The news hour: Welfare estimation in the market for local television news - Baker, Matthew J.; George, Lisa M. (International journal of industrial organization, 2024)
We estimate the welfare consequences of local news broadcasting decisions in advertiser-funded television, a central question in media regulation. We model programming decisions as the outcome of a discrete game played by rival stations competing for advertising revenue (which depends on viewing) by choosing lineups of local news and entertainment broadcasts. Using program-level data on television viewing and advertising prices, we find modest under-provision of local news relative to the level that maximizes television viewing. Counterfactual simulations indicate an average deficit of 7.4 broadcasts per market, or 12.8% of local station broadcasts during the evening news hours. Most of this shortfall is in the 7:30 timeslot leading into prime time. We distinguish two sources of inefficiency: losses due to advertiser valuation of local news and entertainment viewers, and losses from classic business stealing. Losses from competition represent about one third of the estimated shortfall, suggesting gains to cooperation among competing stations. •Media markets are subject to welfare loss from two sources: two-sided market distortions and classic business stealing.•Model estimates indicate that both distortions are present in the US local television market during the evening news hours.•Counterfactual simulations show modest underprovision of local news programming, about 12.8% of local station broadcasts.•Losses from competition represent about one third of the estimated shortfall.